Tempestad en los Andes (Wiström, 2014): On the Construction of the “Victim” Figure in a Documentary About Post-Conflict Peru - Leyva Morillas, Luis Mauricio (2025)
The present article aims to analyze the construction of the figure of the “victim” in the documentary Tempestad en los Andes, directed by Mikael Wiström (2014). It argues that the portrayal of Josefin La Torre as a “victim” is a deliberate operation by the director, who employs a range of audiovisual techniques—such as close-up shots emphasizing facial expressions and gestures—to shape her as such. This construction seeks to generate empathy from the audience to support the memory of “good remembrance”, promoted by Wiström.